VC with a vision - The Star, Richard Lim (2011)
UNIVERSITI Putra Malaysia (UPM) vice-chancellor Datuk Dr. Radin Umar Radin Sohadi is your archetypal early riser, but the morning of Feb 23 was certainly no-run-of-mill start.